(3GdOQ GdfVjO aj TQM GdbUjO (B((3GdTGWHjI(B)s - (3TeS GdOjf CHhYHO Gddg eMeO Hf CMeO Hf YeGQI GdZSGfj GdCfOdSjs; (3GdTGWHj GdebQF GdVQjQ , CHh eMeO,J (B590 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdefaQO HLdGd YXeJg GdoeJbOS Yf GdCTHGg HceGd QHhHjJg s
(3BNQgG (B:s
(3GdRQfH TLQ cHjQ QGFMJg cQGFMI GdCJQL hRfg aYdd , eKd LYaQ haYdd GdcdGe cKjQ hGddg CYde Je GdcJGH Hef Gddg hdWag s
(3GdfSNI HgG MhGTs
(3GdofSNI ebGHdIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdbQGAGJ hGdJLhjOs